(untitled) (Journal of Atomic and Molecular Sciences, 2016)
The interference minimum in the molecular high-order harmonic generation is studied by numerically solving the non-Born-Oppenheimer approximation time-dependent Schrödinger equation. The results show that two kinds of interference minima appear in the high-order harmonic spectrum when the hydrogen molecular ion is exposed to the laser pulse. Furthermore, by adjusting wavelength of the laser as well as initial condition of nucleus, it is found that two kinds of interference minima are ascribed to the molecular structure and the electronic dynamics behavior induced by the laser field, respectively. Besides, the time-frequency distributions and the electron wave packet distributions are calculated to better understand the mechanism of the minimum.